The Inhibitory Of Orange (Citrus sinensis) Waste Extracted With N-Hexana Solution As Antibiotic In Broiler - Haroen, Ucop (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2016)
The experiment was designed to study the uses of orange waste extracts with solution of n-hexana in inhibiting the pathogen bacteria on broilers. Orange wasteextracts with solution n-hexana, E.coli and S.enteridisbacteria, were assigned into the zone of inhibition (Disc) and minimum inhibitory concentration (MIC).Completely randomized design was used in the present study, were randomly allocated to five treatments groups given varying in concentrations of orange waste extracts. P0 = antibiotic, P1 = 250 ppm orange waste extracts, P2 = 500 ppm orange waste extracs, P3 = 750 ppm orange waste extracs and P4 = 1000 ppm orange waste extracts. Supplemented with an antibiotic only was used as a control. The concentrations 1000 ppm of MIC were testshowed inhibition of orange waste extracts higher with a percentage minimum 22,87% for the bacteriumE. coliand 18,99% for the S. enteriditisthan index activity 2,50for the bacterium E. coli and 2,75for the S. enteriditis.